Pushed to the edge : inclusion and behaviour support in schools - Gillies, Val (Policy Press, 2016)
In recent years, a little-noted policy has dramatically transformed - for the worse - the experience of schooling in the United Kingdom for a large number of young people. Internal behavior support units, which ostensibly serve to help manage and improve problematic behavior in students, have been installed in schools throughout the nation, with the result that large numbers of young people are removed from mainstream classrooms for long periods to undergo rehabilitative programs that operate with little oversight. Making use of the insights of young people experiencing these units, this book offers a detailed analysis and critique of this approach, and it should prompt sharp questions from parents, educators, and policy makers alike around issues of social justice, equal opportunities, and institutional racism.